Perancangan User Experience Web Portal Merdeka Belajar FILKOM menggunakan Metode Design Thinking - Miranda Eristiana; Herman Tolle; Intan Sartika Eris Maghfiroh (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
In 2020, the Indonesian Ministry of Education, Culture, Research, and Technology created a program that is useful for improving self-competence for a student, this program is called "Merdeka Belajar-Kampus Merdeka (MBKM)". The implementation of the MBKM Program at the Faculty of Computer Science (FILKOM) has been implemented since the even semester of 2020. However, because this program is a new program created by the government, from FILKOM UB, the implementation of the MBKM program is still not optimal and there are many obstacles at the beginning, such as the delivery of information that is not comprehensive, the collection of administrative files is still done manually. , and the absence of a supporting platform for the delivery of information related to MBKM activities at FILKOM UB. Therefore, in this study the author aims to design a user experience web portal for MBKM FILKOM UB. This website can later be used as a forum for FILKOM UB in conveying information about MBKM activities and can help students or lecturers to support their activities in the MBKM program. The design of the MBKM web portal user experience uses the design thinking method. The design of the solution in this research is in the form of an interactive prototype which will be used at the evaluation stage of prototype testing. The solution design evaluation test was carried out using usability testing to 9 (nine) participants who were classified into 3 (three) different groups, namely active students of FILKOM UB who had never participated in MBKM, active students of FILKOM UB who were registered in MBKM, and MBKM supervisors. This evaluation results in 95% on the effectiveness aspect, 70% on the efficiency aspect, and 83% on the satisfaction aspect. The value of the satisfaction aspect in this study was obtained through the USE Questionnaire which included 4 parameters, namely usefulness, ease of use, ease of learn, and satisfaction. The usability level achieved in the user experience web portal design of MBKM FILKOM UB reaches 83% and is included in the very good category..